PHILOSOPHICAL AND AESTHETIC INTERPRETATIONS OF THE IMAGE OF THE PROTAGONIST IN OSCAR WILDE'S THE HAPPY PRINCE - Rajabova Gulkhanim Bekmirza qizi (International Journal of Literature and Language Studies, 2026)
This article examines the philosophical and aesthetic dimensions of the protagonist in Oscar Wilde's fairy tale The Happy Prince. The study explores how Wilde constructs the image of the Happy Prince as a complex symbolic figure embodying aesthetic beauty, moral consciousness, social responsibility, and spiritual transformation. Using philosophical hermeneutics, aesthetic criticism, and textual analysis, the research investigates the interaction between Victorian aestheticism and ethical humanism represented in the protagonist's character. The findings reveal that the Happy Prince undergoes a significant transformation from a passive symbol of material beauty into an active agent of compassion and sacrifice. The study demonstrates that Wilde challenges the doctrine of